2015
DOI: 10.2478/s11696-014-0595-x
|View full text |Cite
|
Sign up to set email alerts
|

Third-generation oxygen amperometric biosensor based on Trametes hirsuta laccase covalently bound to graphite electrode

Abstract: The response of low-density graphite electrodes hosting Trametes hirsuta laccase in a direct electron transfer regime is presented for real-time analysis of O2 concentrations. The use of contrasting immobilisation methods developed for biocathodes affords good reproducibility and reliability of the amperometric biosensor, which shows a limit of detection below 1 µM and a sensitivity slightly higher than 60 nA cm −2 M −1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The performance of the PGE implemented by direct linking BOx to rGO via PBSE was low (11 ± 3 µA mM −1 cm −2 , n = 3). Both PGE-rGO-MWCNT-BOx and PGE-MWCNT-BOx had higher sensitivity to oxygen when compared with other biosensors referred in the literature [27][28][29][30] . Mousty et al reported a biosensor with a sensitivity value of 470 µA mM −1 cm −2 under stirring conditions but with adding of the ABTS electron mediator 31 .…”
Section: Resultsmentioning
confidence: 78%
“…The performance of the PGE implemented by direct linking BOx to rGO via PBSE was low (11 ± 3 µA mM −1 cm −2 , n = 3). Both PGE-rGO-MWCNT-BOx and PGE-MWCNT-BOx had higher sensitivity to oxygen when compared with other biosensors referred in the literature [27][28][29][30] . Mousty et al reported a biosensor with a sensitivity value of 470 µA mM −1 cm −2 under stirring conditions but with adding of the ABTS electron mediator 31 .…”
Section: Resultsmentioning
confidence: 78%
“…1 mL of EDC 36 mM and 1 mL of NHS 17 mM in PB pH 6.5 were added to this solution, and the reaction was allowed to proceed for 2 h at room temperature. The membrane bioelectrode was then washed using distilled water and kept at 4 °C until use [ 38 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this work, a wireless biosensing application of DET-based oxidoreductase with conductive nanomaterials was demonstrated, and it may open new possibilities for the development of wireless biosensors. Other biosensors based on DET-capable oxidoreductases were demonstrated as well [83][84][85][86][87]. Similarly, DET-capable oxidoreductases were also used in developing third generation bioelectrodes for biofuel cells.…”
Section: Development Of Biosensors and Biofuel Cellsmentioning
confidence: 99%